2018
DOI: 10.31223/osf.io/kxqb2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Dark Fiber and Distributed Acoustic Sensing for Near-Surface Characterization and Broadband Seismic Event Detection

Abstract: We present the first case study demonstrating the use of regional unlit fiber-optic telecommunication infrastructure (dark fiber) and distributed acoustic sensing for broadband seismic monitoring of both near-surface soil properties and earthquake seismology. We recorded 7 months of passive seismic data on a 27 km section of dark fiber stretching from West Sacramento, CA to Woodland, CA, densely sampled at 2 m spacing. This dataset was processed to extract surface wave velocity information using ambient noise … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 21 publications
(25 reference statements)
0
42
0
Order By: Relevance
“…Recent development of the DAS interrogator technology enables us to convert the telecommunication fiber‐optic cables to an array of acoustic sensors that provides continuous measurements of dynamic strain fields in space and time. The feasibility of DAS arrays for recording ground vibrations has been demonstrated in active‐source seismic surveys (Daley et al, ; Mateeva et al, ), ambient noise monitoring (Dou et al, ; Martin et al, ; Zeng et al, ), and earthquake detection (Ajo‐Franklin et al, ; Lindsey et al, ; Wang et al, ; Yu et al, ). Compared to seismometers, the DAS array is composed of up to tens of kilometers of fiber‐optic cable and is transformed into thousands of virtual sensors with spatial sampling along the cable on the scale of meters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent development of the DAS interrogator technology enables us to convert the telecommunication fiber‐optic cables to an array of acoustic sensors that provides continuous measurements of dynamic strain fields in space and time. The feasibility of DAS arrays for recording ground vibrations has been demonstrated in active‐source seismic surveys (Daley et al, ; Mateeva et al, ), ambient noise monitoring (Dou et al, ; Martin et al, ; Zeng et al, ), and earthquake detection (Ajo‐Franklin et al, ; Lindsey et al, ; Wang et al, ; Yu et al, ). Compared to seismometers, the DAS array is composed of up to tens of kilometers of fiber‐optic cable and is transformed into thousands of virtual sensors with spatial sampling along the cable on the scale of meters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies demonstrate that telecommunication optical‐fiber cable networks widely installed in recent decades can be used for DAS recording (Jousset et al, ; Martin et al, ). Both Ajo‐Franklin et al () and Yu et al () demonstrated the value of a 20‐km‐long DAS array using telecommunication fiber optics for recording ambient noise and earthquakes in California. Thus, if thunder‐induced seismic waves can be detected by the DAS fiber‐optic array, the high‐fidelity DAS data would be able to provide the detailed characterization of thunder‐induced ground motions in a local area.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, wireless sensor networks (WSN) and the Internet of Things (IoT) have provided new opportunities for real time and high-resolution monitoring in a distributed network. The (Werner-Allen et al 2006), spatially and temporally continuous air quality monitoring (Boubrima, Bechkit, and Rivano 2017), and earthquake detection from a distributed acoustic sensor network on regional fiber-optic telecommunication infrastructure (Ajo-Franklin et al 2019). Compared to the WSN, an IoT system refers to a large collection of sensors used to individually gather and send data through a router to the Internet.…”
Section: In Situ Sensingmentioning
confidence: 99%
“…Over the past decade, DAS has been a rapidly evolving technology for downhole recording in oil and gas reservoirs (Willis et al, 2016). Recent success of DAS applications using existing telecommunication infrastructures (Jousset et al, 2018;Yu et al, 2019;Ajo-Franklin et al, 2019) demonstrates its cost-effectiveness -2-manuscript submitted to Geophysical Research Letters in deployment and maintenance. However, these experiments are conducted for applications in earthquake seismology in remote areas where anthropogenic noise is rare and desired signals are clearly visible above the random noise in DAS measurements.…”
Section: Introductionmentioning
confidence: 99%